How land use alters the tornado disaster landscape. (May 2018) - Strader, Stephen M.; Ashley, Walker S.; Pingel, Thomas J.; Krmenec, Andrew J.
Abstract: This research assesses how the spatial character of land use influences tornado disaster potential at regional and metropolitan scales. Fine-scale, residential built-environment data for the Central Plains (regional) and Wichita, KS (metropolitan) domains are used in a Monte Carlo tornado simulation framework to estimate significant tornado impact magnitude and disaster potential. The land use patterns of the domains are hypothetically adjusted using the 2010 observed data surface as a baseline to explore how the density and spatial character of land use affects the possibility of significant tornado impacts. As residential built-environment density is reduced and the footprint of developed land grows, tornado impact probability and magnitude increases. Conversely, restricting sprawl while, at the same time, adopting a more concentrated land use pattern, lowers the odds of tornado impact and disaster. Results reveal that the geographic character of land use is important in determining an area's tornado disaster potential. This finding is especially unique and critical for develop proactive disaster mitigation strategies. Pre-disaster mitigation efforts such as effective land planning and building code improvement and enforcement are required to reduce future tornado impacts. Highlights: The geographic character of land use is important in determining an area's tornado disaster potential. Communities with greater development sprawl have a higher overall tornado impact probability. Although communities with greater development sprawl have a higher overall tornado impact probability. A greater emphasis should be placed on preemptive and proactive mitigation strategies to reduce disaster probability. Results may assist government decision makers as they decide where to direct available tornado risk mitigation funding.